Light-Activated Monomethyl Auristatin E Prodrug Nanoparticles for Combinational Photo-Chemotherapy of Pancreatic Cancer - Cho, In Kyung; Shim, Man Kyu; Um, Wooram; Kim, Jong-Ho; Kim, Kwangmeyung (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Pancreatic cancer is a highly fatal disease that is becoming an increasingly leading cause of cancer-related deaths. In clinic, the most effective approach to treat pancreatic cancers is the combination treatment of several chemotherapeutic drugs, including fluorouracil, leucovorin, irinotecan, and oxaliplatin (FOLFIRINOX), but this approach is not adequate to manage patients due to their severe toxic side effects. Herein, we proposed light-activated monomethyl auristatin E (MMAE) prodrug nanoparticles for combinational photo-chemotherapy and optimized its applications for pancreatic cancer treatment. The photosensitizer (Ce6) and chemotherapeutic drug (MMAE) were conjugated through caspase-3-specific cleavable peptide (KGDEVD). The resulting CDM efficiently promoted the reactive oxygen species (ROS) under visible light irradiation and thereby induced caspase-3 overexpression in pacreatic cancers, which subsequently released the MMAE from the system. Importantly, MMAE released from CDM further amplified the activation of CDM into MMAE by inducing extensive apoptotic cell death in tumor microenvironment for treatment of tumor cells in deep in the tumor tissues as far visible light cannot reach. In addition, CDM formed prodrug nanoparticles via intermolecular pi-pi stacking and hydrophobic interactions, allowing durable and reliable treatment by preventing fast leakage from the pancreatic cancers via the lymphatic vessels. The CDM directly (intratumoral) injected into pancreatic cancers in orthotopic models through an invasive approach significantly delayed the tumor progression by combinational photo-chemotherapy with less toxic side effects. This study offers a promising and alternative approach for safe and more effective pancreatic cancer treatment via prodrug nanoparticles that combine photodynamic therapy and chemotherapy.